Neonatal encephalopathic cerebral injury in south india assessed by perinatal magnetic resonance biomarkers and early childhood neurodevelopmental outcome - Lally,PJ; Price,DL; Pauliah,SS; Bainbridge,A; Kurien,J; Sivasamy,N; Cowan,FM; Balraj,G; Ayer,M; Satheesan,K; Ceebi,S; Wade,A; et al. (PLOS One, 2014)
Although brain injury after neonatal encephalopathy has been characterised well in high-income countries, little is known about such injury in low- and middle-income countries. Such injury accounts for an estimated 1 million neonatal deaths per year. We used magnetic resonance (MR) biomarkers to characterise perinatal brain injury, and examined early childhood outcomes in South India.MethodsWe recruited consecutive term or near term infants with evidence of perinatal asphyxia and a Thompson encephalopathy score ≥6 within 6 h of birth, over 6 months. We performed conventional MR imaging, diffusion tensor MR imaging and thalamic proton MR spectroscopy within 3 weeks of birth. We computed group-wise differences in white matter fractional anisotropy (FA) using tract based spatial statistics. We allocated Sarnat encephalopathy stage aged 3 days, and evaluated neurodevelopmental outcomes aged 3½ years using Bayley III.ResultsOf the 54 neonates recruited, Sarnat staging was mild in 30 (56%); moderate in 15 (28%) and severe in 6 (11%), with no encephalopathy in 3 (6%). Six infants died. Of the 48 survivors, 44 had images available for analysis. In these infants, imaging indicated perinatal rather than established antenatal origins to injury. Abnormalities were frequently observed in white matter (n=40, 91%) and cortex (n=31, 70%) while only 12 (27%) had abnormal basal ganglia/thalami. Reduced white matter FA was associated with Sarnat stage, deep grey nuclear injury, and MR spectroscopy N-acetylaspartate/choline, but not early Thompson scores. Outcome data were obtained in 44 infants (81%) with 38 (79%) survivors examined aged 3½ years; of these, 16 (42%) had adverse neurodevelopmental outcomes.ConclusionsNo infants had evidence for established brain lesions, suggesting potentially treatable perinatal origins. White matter injury was more common than deep brain nuclei injury. Our results support the need for rigorous evaluation of the efficacy of rescue